2018
DOI: 10.1016/j.urology.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Diabetes Insipidus After Pyeloplasty: A Case Report and Review of the Literature

Abstract: Nephrogenic diabetes insipidus (NDI), a rare cause of polyuria and polydipsia in children, is usually managed with medications and careful monitoring of water intake. We present a child who was incidentally found to have right hydronephrosis secondary to ureteropelvic junction obstruction, and was subsequently also diagnosed with NDI. After being medically managed, he underwent open right pyeloplasty. His polydipsia abated within 1 month of surgery, and he has done well off of medications since that time. NDI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It is worth noting that hydronephrosis and/ or deterioration of renal function may recur a few years after spontaneous resolution of hydronephrosis, and it is usually accompanied by symptoms, such as abdominal pain, nausea, vomiting, and hematuria (16). Carpenter et al (8) reported that patients should undergo continuous careful monitoring postoperatively if symptoms persist, such as polydipsia and polyuria. The clinical/surgical approach has changed a lot and plays a positive role in the preservation of renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that hydronephrosis and/ or deterioration of renal function may recur a few years after spontaneous resolution of hydronephrosis, and it is usually accompanied by symptoms, such as abdominal pain, nausea, vomiting, and hematuria (16). Carpenter et al (8) reported that patients should undergo continuous careful monitoring postoperatively if symptoms persist, such as polydipsia and polyuria. The clinical/surgical approach has changed a lot and plays a positive role in the preservation of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no studies or guidelines that indicate the specific follow-up intervals and surgical indications for mild hydronephrosis if predisposing risk factors persist. DI causes non-obstructive hydronephrosis (8); however, to the best of our knowledge, no studies have shown whether DI can cause or aggravate obstructive hydronephrosis. This article describes a case of asymptomatic obstructive hydronephrosis that was aggravated by DI.…”
Section: Introductionmentioning
confidence: 90%